2017
DOI: 10.1080/0284186x.2016.1266086
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with sex life in sexually active heterosexual couples dealing with breast cancer: a nationwide longitudinal study

Abstract: Satisfaction with sex life in sexually active couples dealing with BC needs to be seen as a couple issue. Health professionals should take the partner into account when addressing sexuality issues. Couples' functioning and relationship-related factors may be promising targets for couple interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Of the three relationship-related variables in the present study this rating of behavior is potentially most closely related to the behavioral outcome sexual activity, and couples agree rather strongly on the occurrence of this type of behavior in their relationship (within-couple correlation r = 0.68). Previous research has shown that affectionate behavior also is associated with other sexual health indicators, such as satisfaction with sex life ( Fisher et al, 2015 ; Rottmann et al, 2017 ). However, there is also a relatively large subgroup of couples at baseline that report frequent affectionate behavior but no sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three relationship-related variables in the present study this rating of behavior is potentially most closely related to the behavioral outcome sexual activity, and couples agree rather strongly on the occurrence of this type of behavior in their relationship (within-couple correlation r = 0.68). Previous research has shown that affectionate behavior also is associated with other sexual health indicators, such as satisfaction with sex life ( Fisher et al, 2015 ; Rottmann et al, 2017 ). However, there is also a relatively large subgroup of couples at baseline that report frequent affectionate behavior but no sexual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in most cases, women are not informed about the possibilities of dealing with this problem. The diagnosis and consequences of treatment affect intimate relationships [38]. Relationship with one's partner is a very important factor that determines the psychosocial health of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the diagnosis and the associated treatments of breast cancer, profound psychological and physical consequences often result. These consequences often have an impact on the quality of life of women [ 8 , 9 ], and their sexual functioning and satisfaction [ 10 , 11 ]. Previous research has found that the variables related to quality of life of women with breast cancer were age [ 12 , 13 ]; current treatments with associated side effects, such as chemotherapy or radiotherapy [ 14 ]; level of family support [ 15 ]; symptoms of anxiety and depression [ 16 ]; and body image [ 7 ].…”
Section: Introductionmentioning
confidence: 99%